Same-Sex Marriages : Legal Issues. (U.S. Congressional Research., 2009)
Discusses legal issues surrounding same-sex marriages and P.L. 104-199, the Defense of Marriage Act (DOMA), which prohibits Federal recognition of same-sex marriages. Examines potential constitutional challenges to DOMA; interstate recognition of marriage; State litigation, constitutional amendments, and civil union laws; and pending Federal legislation.